People With Disabilities Need Lawyers Too! A Ready-To-Use Plan for Law Schools to Educate Law Students to Effectively Serve the Legal Needs of Clients With Disabilities as Well as Clients Without Disabilities - Lepofsky, David (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2022)
Canada's legal profession is not sufficiently equipped to meet the legal needs of clients with disabilities. For decades, legal education focused primarily, if not exclusively, on training law students to serve clients without disabilities. A law student can complete their legal education while learning little about how to meet the legal needs of clients with disabilities. Law students need to be effectively trained to serve clients with disabilities as well as clients with no disabilities. Law faculties commendably focus increasingly on Equity, Diversity, and Inclusion. Disability should be a strong and equal focus in their equity, diversity and inclusion strategies. How can a law school fix this? This article gives a roadmap, and gives further resources enabling law deans and law teachers to quickly take action. This article first describes why it is important to expand a law school's disability curriculum. It spells out disability content that should be shared with students, including a course-by-course delineation of topics. It offers practical, cost-effective options for law schools to systematically work towards permanently embedding disability content in their programs. A law school should make a concerted policy decision and create an action plan. This article’s tools point the way.